Correlation of Urine Albumin/Creatinine Ratio (UACR), High Sensitivity C-Reactive Protein (hsCRP) and N-Terminal Pro Brain Natriuretic Peptide (NT-proBNP) with Atherosclerosis (OxLDL) in Centrally Obese Men - Nancy Pakpahan; Mansyur Arif; Ilhamjaya Patellongi (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Obesity is closely associated with atherosclerosis risk and cardiovascular disease. Novel cardiovascular risk biomarkers such as Urine Albumin/Creatinine Ratio (UACR), High Sensitivity C-Reactive Protein (hsCRP) and N-Terminal pro Brain Natriuretic Peptide (NT-proBNP) have been observed to predict cardiovascular disease in the general population. The aim of this study was to observe the correlation of UACR, hsCRP and NT-proBNP with atherosclerosis (OxLDL) in centrally obese men.METHODS: The study was observational with a cross sectional design done on 76 male subjects aged 30–50 years with central obesity and mean of age of 37 years. Urine albumin was determined by PEG enhanced immunoturbidimetric assay, urine creatinine by Jaffe without deproteinase, hsCRP by chemiluminescent immunometric assay, NT-proBNP by electrochemiluminescence (ECLIA) and OxLDL by ELISA.RESULTS: There was significant correlation between hsCRP and OxLDL (r=0.230, p=0.046). There was no significant correlation between UACR and OxLDL (r=-0.138, p=0.236), neither between Log NT-proBNP and OxLDL (r=-0.173, p=0.136).CONCLUSIONS: Atherosclerosis was significantly correlated with hsCRP (low grade inflammation).KEYWORDS: NT-proBNP, UACR, hsCRP, OxLDL, atherosclerosis